Effect of a coating based on chitosan and onion extract on useful life and sensory characteristics of Mahi-Mahi fillets in cooling - Betún Beltrán, Dolores; Martínez Valenzuela, Gustavo Elías; Cantillo Holguín, Génesis Nathaly (Journal of the University of Zulia, 2022)
Fishing products are highly susceptible to deterioration due to various causes, bacterial growth is the main factor that limits their useful life. The present investigation evaluated the effect of a coating based on chitosan and onion extract on the useful life and sensory characteristics of Mahi-Mahi fillets. The coating with the highest sensory acceptance was T6 made with 3% chitosan and 1% onion extract, which obtained values below the permissible ranges in the current legal standard up to 21 days in refrigeration (29.12 mg N / 100 g). The microbiological analysis showed the absence of mesophilic aerobes until the seventh day of storage in refrigeration, gradually increasing their count until 21 days (1.9x103 CFU / g), complying with the provisions of current legal regulations (1x105 CFU / g), likewise, the absence of total coliforms and E. coli was verified during the established time.